169 Real world nhs experience of ctca with ffrct for the detection of surgical coronary artery disease - the case for enhanced pre-procedural planning?. (4th June 2021) - Murphy, David; Graby, John; Rakheca, Tushar; Donaghue, Jessica; McKenzie, Dan; Kandan, Sri Raveen; Khavandhi, Ali; Carson, Kevin; Lowe, Rob; Hudson, Ben; Rodrigues, Jonathan
Abstract : Introduction: CT coronary angiography (CTCA) with fractional flow reserve (FFRCT) is a key diagnostic tool in the guidance led evaluation of chronic coronary syndrome (CCS). A small percentage of those patients presenting with CCS will have a pattern of coronary artery disease (CAD) where they would be better served with surgical revascularisation. CTCA alone is increasingly used to rule out important CAD pre-valvular surgery in the absence of an invasive coronary angiogram (ICA). Thus, this study tested to see if CTCA with FFRCT was sufficient to predict surgical CAD relative to subsequent ICA findings. Methods: This retrospective single-centre study analysed all patients with CCS who underwent a CTCA with FFRCT, where findings led to a subsequent ICA from August 2018 to January 2021. Those patients who had significant left main stem (LMS) and/or flow limiting disease in three major epicardial blood vessels were included (3VD). Flow limiting disease was defined as an FFRCT of ≤0.8 (2 cm distal to the stenosis) in the left anterior descending (LAD), circumflex (LCx), principle obtuse marginal (OM) or right coronary artery (RCA). This was then compared to the ICA where significance was defined as a stenosis >50% for the LMS and >70% for the other epicardial vessels and/or iFR of ≤0.89 or FFR ≤0.8. Results: A total of 565 patients had a CTCA with FFRCT, of which 164 had a subsequent ICA with sufficient data for analysis and 35 of these patients met inclusion criteria (LMS disease only 7/35, 3VD 25/35 and both LMS and 3VD 3/35 on CTCA with FFRCT). Relative to ICA the overall sensitivity, specificity, positive predictive value, negative predictive value and accuracy of CTCA and FFRCT for predicting surgical CAD was 83% (95% CI 61-95), 92% (95% CI 86-96), 61% (95% CI 47-74), 97% (95% CI 93-99) and 90% (95% CI 85-94) respectively. Conclusion: CTCA with FFRCT was insufficient for a direct decision on surgical revascularisation in this cohort, particularly given the different risk profiles of ICA, PCI and bypass surgery. Importantly, however, the performance of CTCA with FFRCT for detection of surgical CAD would enable enhanced pre-procedural planning. This includes providing an opportunity to counsel patients in more detail on potential findings and their preference if a surgical pattern of disease is confirmed, consider pre-ICA MDT discussion, and ensure likely complex, high-risk cases are placed on an appropriate list. Conflict of Interest: None